Kualitas Pelayanan Unit Aviation Security dalam Pemeriksaan Penumpang dan Bagasi di Security Check Point Bandar Udara Kelas I Merauke - Pohan, Farida Romaito; Ningrum, Nur Rohmah Yulia; Bangkit Wibowo, Juventus (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
This research aims to determine the service quality of the Aviation Unit (Avsec) in checking passengers and baggage at the Security Check Point (SCP) of Merauke Class I Mopah Airport. The method used in this research is a qualitative method using data collection techniques through interviews, observation, and documentation. Data were analyzed using interactive analysis, which consists of three stages, namely, data condensation, data presentation, and drawing conclusions. The research results show that the level of passenger satisfaction with the services of Aviation Security (Avsec) officers is considered satisfactory. The officers have carried out their duties well in checking passengers and baggage which will ensure the safety and security of passengers at Merauke Class I Mopah Airport. Supporting factors are reliability and expertise in carrying out tasks in accordance with their field, supporting airport facilities and infrastructure as well as friendly and polite officers in serving passengers. Meanwhile, the inhibiting factor is the low level of discipline, which causes delays in service to passengers.